The Influence Of Product Quality, Price, And Service Quality On Customer Satisfaction Of Sr12 Skincare Products At We Store In Bengkulu City - Hidayati, Ismi; Abi, Yudi Irawan; Febliansa, Muhammad Rahman (Utami Publisher, 2025)
The sample in this study was 100 people who had used SR12 skincare products for 3 months and customers of WE Store in Bengkulu City. The data collection technique used a questionnaire. The analysis method used was multiple regression analysis, t-hypothesis test and f-hypothesis test. The results of the regression equation are Y = 19.531 + 0.117 X₁ + 0.134 X₂ + 0.110 X₃. meaning the influence of product quality, price, and service quality on customer satisfaction of SR12 skincare products at WE Store in Bengkulu City. The significance value of each variable is below 0.05, indicating a real influence. In addition, the three variables together affect customer satisfaction by 81.4%, while the remaining 18.6% is influenced by other factors outside this study.